231k views
4 votes
Urgent help pleaseeeeeee

Urgent help pleaseeeeeee-example-1
User EddieB
by
6.1k points

2 Answers

7 votes

Answer:

2x - 10 = 10 - 3x

Simplifying

2x + -10 = 10 + -3x

Reorder the terms:

-10 + 2x = 10 + -3x

Solving

-10 + 2x = 10 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.

-10 + 2x + 3x = 10 + -3x + 3x

Combine like terms: 2x + 3x = 5x

-10 + 5x = 10 + -3x + 3x

Combine like terms: -3x + 3x = 0

-10 + 5x = 10 + 0

-10 + 5x = 10

Add '10' to each side of the equation.

-10 + 10 + 5x = 10 + 10

Combine like terms: -10 + 10 = 0

0 + 5x = 10 + 10

5x = 10 + 10

Combine like terms: 10 + 10 = 20

5x = 20

Divide each side by '5'.

x = 4

Simplifying

x = 4

User Biser
by
6.3k points
6 votes

Answer

pick C

Explanation:

the answer is 2x+12

User William Troup
by
5.4k points